Dynamic transmission modelling to address infant pneumococcal conjugate vaccine schedule modifications in the UK. Issue 14 (17th July 2018) - Wasserman, M.; Lucas, A.; Jones, D.; Wilson, M.; Hilton, B.; Vyse, A.; Madhava, H.; Brogan, A.; Slack, M.; Farkouh, R.
Abstract: The 13-valent pneumococcal conjugate vaccine (PCV) has been part of routine immunisation in a 2 + 1 schedule (two primary infant doses and one booster during the second year of life) in the UK since 2010. Recently, the UK's Joint Committee on Vaccination and Immunisation recommended changing to a 1 + 1 schedule while conceding that this will increase disease burden; however, uncertainty remains on how much pneumococcal burden – including invasive pneumococcal disease (IPD) and non-invasive disease – will increase. We built a dynamic transmission model to investigate this question. The model predicted that a 1 + 1 schedule would incur 8777–27 807 additional cases of disease and 241–743 more deaths over 5 years. Serotype 19A caused 55–71% of incremental IPD cases. Scenario analyses showed that booster dose adherence, effectiveness against carriage and waning in a 1 + 1 schedule had the most influence on resurgence of disease. Based on the model assumptions, switching to a 1 + 1 schedule will substantially increase disease burden. The results likely are conservative since they are based on relatively low vaccine-type pneumococcal transmission, a paradigm that has been called into question by data demonstrating an increase of IPD due to several vaccine serotypes during the last surveillance year available.